Supply Chain Implementation Strategy InThe SPPG Kitchen Network Area AsA Solution To SPPG Problems In Indonesia - Nabaraj Bhowmik; Dipangshu Dev Chowdhury; Andri Hermawan (Ann Publisher, 2026)
Background.The SPPG Kitchen Program has been running for more than a year as an effort to meet the food needs of the beneficiary communities. Although it has shown various progress, its implementation still faces a number of obstacles that have an impact on service quality, including the suspension of around 1500 SPPG units. Aims.This research aims to analyze problems in the implementation of SPPG and formulate effective supply chain implementation strategies.Methods.The methodology used includes stakeholder mapping, food safety, and K3 knowledge gap analysis, and cause-and-effect analysis. In addition, the SCOR (Supply Chain Operations Reference) model approach and SWOT analysis are used to deepen the evaluation of supply chain systems.Result.The results of the study show that the main problems lie in the disintegration of the supply chain, differences in stakeholder interests, and low human resource capacity. Recommended strategies include system integration, process simplification, human resource capacity building, and strengthening local ecosystems. Implementation.The implementation of this strategy is expected to improve the efficiency, stability, and quality of SPPG services.